2011
DOI: 10.1002/ajmg.a.34052
|View full text |Cite
|
Sign up to set email alerts
|

Early ultrasound suspect of thanatophoric dysplasia followed by first trimester molecular diagnosis

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
5
2
Order By: Relevance
“…Measurement of the fetal foot was performed retrospectively and not during the NT scan session which is prone to bias despite that those measurements were obtained unknowingly corresponding to cases or controls. Compared to other publications that reported a higher rate of diagnosis of skeletal dysplasia in the first trimester, 7,8,17 the majority of our cases were diagnosed with skeletal dysplasia after but not during the NT scan;…”
Section: Strengths and Limitationscontrasting
confidence: 91%
See 2 more Smart Citations
“…Measurement of the fetal foot was performed retrospectively and not during the NT scan session which is prone to bias despite that those measurements were obtained unknowingly corresponding to cases or controls. Compared to other publications that reported a higher rate of diagnosis of skeletal dysplasia in the first trimester, 7,8,17 the majority of our cases were diagnosed with skeletal dysplasia after but not during the NT scan;…”
Section: Strengths and Limitationscontrasting
confidence: 91%
“…Few case reports identified extremely shortened femur with or without thickened NT at 11-12 weeks' gestation as the initial sonographic finding prompting molecular testing to confirm skeletal dysplasia. 7,8,17 In our study, we observed that pregnancies affected by skeletal dysplasia especially of lethal types had shortened femur during the NT screen. However, we consider that unless an extremely shortened or distorted femur also is identified, relying solely on a first trimester FL to screen for skeletal dysplasia is not practical since most available biometric charts including FL begin at 14 weeks' gestation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The earliest radiological signs are increased nuchal thickness and short limbs, but these signs are nonspecific. 5,6 A molecular diagnosis may be made prenatally if genetic testing for TD is requested on deoxyribonucleic acid (DNA) extracted from a chorionic villus or amniocentesis sample, but is more commonly made following a post-mortem examination carried out to clarify the nature of the lethal skeletal dysplasia in question. 5,6 TD is primarily an autosomal dominant disorder, resulting from heterozygous mutations in the FGFR3 gene that lead to ligand-independent activation of the receptor and disruption of cartilage function during linear bone growth.…”
mentioning
confidence: 99%
“…5,6 A molecular diagnosis may be made prenatally if genetic testing for TD is requested on deoxyribonucleic acid (DNA) extracted from a chorionic villus or amniocentesis sample, but is more commonly made following a post-mortem examination carried out to clarify the nature of the lethal skeletal dysplasia in question. 5,6 TD is primarily an autosomal dominant disorder, resulting from heterozygous mutations in the FGFR3 gene that lead to ligand-independent activation of the receptor and disruption of cartilage function during linear bone growth. 7 Mutations in the FGFR3 gene cause a spectrum of skeletal dysplasias ranging from the relatively mild hypochrondroplasia through to achondroplasia, severe achondroplasia with developmental delay and acanthosis nigricans (SADDAN), and thanatophoric dysplasia.…”
mentioning
confidence: 99%